Physiological and Hematological Responses in Cantang Grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus) Against the Salinity of Different Media - Larasati, Anastasya Dewi; Widodo, Langgeng; Melinda Kusuma Ningrum; Ridwansyah; Karunia, Fitria; Sulmartiwi, Laksmi; Mahasri, Gunanti; Triastuti, Rr Juni; Lutfiyah, Lailatul (Department of Aquaculture, 2025)
Fish Cantang grouper is a cross between a female tiger grouper (Ephinepelus fuscoguttatus) and a male kertang grouper (Ephinepelus lanceolatus), has a high economic value. Salinity is a water quality factor that affects cultivation because salinity has osmotic pressure that can cause changes in physiological activity and stress in fish if it is not in accordance with the habitat. Stress in fish causes the release of cortisol and catecholamine hormones. The catecholamine hormone then increases the glycogenolysis process, regulates cardiovascular and respiratory function, in addition to increasing cortisol and blood glucose. Stress in fish is also indicated by a hematological response in the form of changes in the number of erythrocytes. This study aims to determine the effect of different salinity treatments on physiological and hematological responses. The results of the analysis of variance (ANOVA) carried out from the initial observation to 24 hours showed that each salinity treatment had a significantly different effect on blood cortisol, blood glucose, and erythrocyte levels, with a value (p <0.05). The highest average blood cortisol was in the 36 ppt treatment at 24-hour observation time. The average blood glucose increased from before being treated, until receiving treatment for up to 24 hours. The highest average was obtained at a salinity of 36 ppt, with observation for 24 hours. The results obtained from the study showed that the highest number of erythrocyte cells at 24 hours was in the P2 treatment (36 ppt), namely 1.15 x 106 cells/mm³.